?SPECTROPHOTOMETERIC DETERMINA TION OF METALS IN PAAISTANI AND FOREIGN BRAND CIGARETTE TOBACCO ? Short Communication (Biological Sciences - PJSIR, 2001)
Tobacco smoking and related uses are a major cause of various diseases in human beings (Bartecchi et at 1995:philips1996). A study on the nature and quantities of many elements present in tobacco leaves is important to the tobacco and health researchers (Sato et al 1977).